Samorządy zawodów zaufania publicznego w dobie transformacji cyfrowej. Perspektywy i wyzwania na przykładzie samorządu notarialnego - Bodzenta, Krzysztof (PRAWO i WIĘŹ, 2025)
This paper addresses the issue of the role of professional self-governments of public trust professions in the process of digital transformation of the state. The aim of the study is to demonstrate the potential of these bodies as active participants in digitization processes, using the example of the notarial self-government. The first part outlines the legal foundations of professional self-governments. This is followed by an analysis of general digitization trends at the EU and national levels. Subsequently, the activities of the notarial self-government in the area of digitization are discussed, indicating both its achievements to date and potential development paths along with the associated challenges. The paper concludes with a summary of the key findings.